Bibliometric analysis of publications on the problem of forming information culture of a person - O. L. Churasheva (Библиосфера)
The article reveals the results of bibliometric analysis of publications on the problem of forming personal information culture presented in Russian scientific journals during 2007-2013. The most productive authors and groups investigating the questions of information culture are identified; geographical, industrial and thematic structure of the document flow on the issue are considered; the productivity of scientific journals publishing articles on the forming personal information culture is analyzed.